Catalyst-Free Decarboxylative Fluorination of Tertiary β-Keto Carboxylic Acids - Katada, Misaki; Kitahara, Kazumasa; Iwasa, Seiji; Shibatomi, Kazutaka (Synlett, 2018)
Decarboxylative fluorination of tertiary β-keto carboxylic acids was performed using an electrophilic fluorinating reagent. The reaction proceeded in the absence of a catalyst or base to yield the corresponding α-fluoroketones with tertiary fluorocarbons in good to high yields. Considering that the α-fluorination of asymmetrical ketones often causes problems with the regioselectivity between the α- and α′-positions, this method could be a good alternative to the α-fluorination of simple ketones for the synthesis of tertiary fluoroketones.
Keywords: fluorination; decarboxylation; α-fluoroketones; noncatalytic reaction; tertiary fluorides